Incidence of gastric adenocarcinoma among lesions diagnosed as low‐grade adenoma/dysplasia on endoscopic biopsy: A multicenter, prospective, observational study. Issue 2 (7th December 2017) - Maekawa, Akira; Kato, Motohiko; Nakamura, Takeshi; Komori, Masato; Yamada, Takuya; Yamamoto, Katsumi; Ogiyama, Hideharu; Nakahara, Masanori; Kawai, Naoki; Yabuta, Takamasa; Mukai, Akira; Hayashi, Yoshito; et al.
Abstract : Background and Aim: Differentiation between gastric adenocarcinoma and low‐grade adenoma/dysplasia (LGA) on endoscopic forceps biopsy is difficult. We aim to clarify the incidence of carcinoma in specimens, obtained by endoscopic resection (ER), from cases that had been diagnosed as LGA (Vienna category 3) on endoscopic biopsy. Methods: In this multicenter, prospective, observational study, patients with gastric adenoma (Vienna category 3 or 4.1) diagnosed on endoscopic forceps biopsy were enrolled. All the specimens were subjected to histopathological central review. Primary endpoint was the incidence of carcinoma (Vienna category 4.2 or over) among the biopsy‐proven gastric LGA. Secondary endpoints were the histological findings of resected specimens, clinicopathological features of carcinoma, and short‐term outcomes of all ER cases. Results: Ninety‐five patients with 104 lesions diagnosed as gastric adenoma were enrolled. After central review of the biopsy specimens, 47 lesions were diagnosed as LGA and seven lesions (15%) as adenocarcinoma (95% confidence interval, 7.6–28%). Carcinoma was detected in lesions that had a minimum size of 6 mm; the incidence of carcinoma was higher in the larger lesions. There was a histological discrepancy between biopsy and ER material in more than 60% of the cases. Conclusions: A substantial proportion of biopsy‐proven gastric LGA specimens were diagnosed as adenocarcinoma after ER. This indicated histological discrepancy between biopsy‐proven gastric LGA and histology of the resected material.